Collaborative modeling of an implementation strategy: a case study to integrate health promotion in primary and community care - Grandes, Gonzalo (BMC Res Notes, 2017)
BACKGROUND: Evidence-based interventions are more likely to be adopted if practitioners collaborate with researchers to develop an implementation strategy. This paper describes the steps to plan and execute a strategy, including the development of structure and supports needed for implementing proven health promotion interventions in primary and community care. RESULTS: Between 10 and 13 discussion and consensus sessions were performed in four highly-motivated primary health care centers involving 80% of the primary care staff and 21 community-based organizations. All four centers chose to address physical activity, diet, and smoking. They selected the 5 A’s evidence-based clinical intervention to be adapted to the context of the health centers. The planned implementation strategy worked at multiple levels: bottom-up primary care organizational change, top-down support from managers, community involvement, and the development of innovative e-health information and communication tools. Shared decision making and practice facilitation were perceived as the most positive aspects of the collaborative modeling process, which took more time than expected, especially the development of the new e-health tools integrated into electronic health records. CONCLUSIONS: Collaborative modeling of an implementation strategy for the integration of health promotion in primary and community care was feasible in motivated centers. However, it was difficult, being hindered by the heavy workload in primary care and generating uncertainty inherent to a bottom-up decision making processes. Lessons from this experience could be useful in diverse settings and for other clinical interventions. Two companion papers report the evaluation of its feasibility and assess quantitatively and qualitatively the implementation process.